Effect of Gender on the Use of Food Markers in Selected Iranian Novels based on Markedness Theory - Azadeh Sharifi Moghaddam; Mahdyeh Dehghani (مطالعات زبانی و بلاغی)
Various kinds of Food not only have physiological and biological functions, but are integrated into our social and cultural systems. As part of our cultural semiotics system, food forms a continuum on which different marked and unmarked food elements are arranged. Like other semiotic systems, food items are influenced by cultural and social factors. In order to investigate the effect of the authors’ gender on the use of food elements, a number of 12 novels from contemporary male and female authors were selected and analyzed. In both gender groups, unmarked items were used more frequently than the marked items. However, the function of items used in each group was different. In the works of male novelists, the frequency of the unmarked food items was higher than the opposite group. However, female novelists used a wider variety and diverse types of unmarked foods. Regarding the marked category, both frequency and diversity of the marked elements were significantly higher in women's texts. The common marked features identified in the texts belonging to both groups were ‘happiness’, ‘belief’ and ‘empathy’, but there was no case for ‘wealth’ in the men's novels. The findings of this research indicate a significant relationship between gender and food function in the corpus of the study. The variety of food and the greater number of these items in the works of female writers are consistent with the preoccupations and concerns of Iranian women compared to men. The findings of the present research show an iconic relationship between the cultural and social tendencies of two gender groups and its representation in their works.